1983
DOI: 10.1126/science.6836285
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress Induces Sodium and Fluid Retention in Men at High Risk for Hypertension

Abstract: Exposure to competitive mental tasks significantly reduced the urinary sodium and fluid excreted by young men with one or two hypertensive parents or with borderline hypertension. In this high-risk group, the degree of retention was directly related to the magnitude of heart rate increase during stress, suggesting common mediation by way of the sympathetic nervous system. Thus, psychological stress appears to induce changes in renal excretory functions that may play a critical role in long-term blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
2
6

Year Published

1985
1985
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(78 citation statements)
references
References 14 publications
5
65
2
6
Order By: Relevance
“…8 We used the same methods as the Belgian studies in determining associations between hypertension or a family history of hypertension, but had no effect on urinary sodium excretion in the urinary sodium excretion and BP as well as for interactions between the urinary sodium excretion young adult men with a negative history of hypertension. 17 The lack of sodium retention shown in the and heart rate. Thus, the lack of evidence for the interaction between heart rate and the urinary low risk subjects who were high heart rate reactors also indicates that cardiovascular and renal symsodium excretion cannot be explained either by a pathetic responses do not always occur on a paralassociated with clinic systolic (P = 0.05) and diastolic (P = 0.08) BP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 We used the same methods as the Belgian studies in determining associations between hypertension or a family history of hypertension, but had no effect on urinary sodium excretion in the urinary sodium excretion and BP as well as for interactions between the urinary sodium excretion young adult men with a negative history of hypertension. 17 The lack of sodium retention shown in the and heart rate. Thus, the lack of evidence for the interaction between heart rate and the urinary low risk subjects who were high heart rate reactors also indicates that cardiovascular and renal symsodium excretion cannot be explained either by a pathetic responses do not always occur on a paralassociated with clinic systolic (P = 0.05) and diastolic (P = 0.08) BP.…”
Section: Resultsmentioning
confidence: 99%
“…At a sodium excretion of lel. 17 In animal studies, a high sodium intake has enhanced selectively the magnitude of the renal 100 mmol/24 h (10th percentile or less), increasing stress from low to high was associated with a fall sympathetic nerve activity and antinatriuretic responses to stressful environmental stimulation, eg, both in systolic (by 4.5 mm Hg) and diastolic (by 1.4 mm Hg) BP. Conversely, at a sodium excretion of mean arterial BP and heart rate responses, which were not increased.…”
Section: Resultsmentioning
confidence: 99%
“…Murphy et al 46 found higher levels of cardiovascular reactivity in black compared with white third graders. Another study by Light et al 47 found a direct correlation between the magnitude of the reduction in urinary sodium and water excretion and the rise in heart rate in young men who were subjected to mental stress. In animals, identical renal responses to stress appear to be mediated by the sympathetic nervous system.…”
Section: Mechanisms and Modifiers Of The Salt-bloodmentioning
confidence: 94%
“…5,6 Furthermore, during stress sodium retention is known to manifest itself particularly in genetically predisposed individuals. 7 change during the stressor were positively correlated (r = 0.75, P Ͻ 0.01). Both groups, however, demonstrated a similar pattern of sodium excretion to mental challenge.…”
Section: Introductionmentioning
confidence: 95%